The case against drug prohibition - Orriols, Alexandra; Thompson, Winston; McAndrews, Megan; Block, Walter E. (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The case against drug prohibition is overwhelming. This law is to drugs what alcohol prohibition was to those substances: a disaster. Drug use, by and among consenting adults, is a victimless crime: it preys on the poor, lifts our inmate population into the stratosphere, has negative racial connotations and leads to needless deaths
Keywords: narkotyki; prohibicja; wolność gospodarcza; rasizm